Book cover inventory (in the latest literature) - Lachman, Magdalena (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
The change in the context of the functioning of literature since 1989 and the transformations contemporary literary life has been subject to due to various reasons have resulted in the need to add a literary science reflection on the latest or not yet fully used up thematic areas. One of the notions worth raising, which increasingly seizes the attention of researchers as well as literary critics, is the issue of the book cover considered as a significant element of the work and its non-neutral identifier. The article defines what kind of a source of knowledge on the work and its author the book cover has become; how writers themselves define themselves through it; how they use it to characterize or present themselves or clarify the strategies they choose; how literature functions and copes while being subjected to the influence of mass culture and various marketing actions or the influence of celebrity-based and (self)promotionally focussed pop culture.